Digital Criminal Law Policy: Ethical and Privacy Challenges In the Enforcement of The New Indonesian Criminal Code (Kuhp) On Cybercrime - Dewi Ervina Suryani; Adinda Azhari; Ahmad Yani Anshori (Program Pascasarjana UIN Sumatera Utara Medan, 2020)
The rapid advancement of digital technology has significantly transformed social interactions, economic activities, and legal systems, while simultaneously creating new forms of cybercrime that challenge conventional criminal law. Indonesia has responded to these developments through the enactment of the new Criminal Code (KUHP), which seeks to modernize the national criminal justice system by incorporating provisions relevant to digital offenses. This study aims to analyze Indonesia's digital criminal law policy under the new Criminal Code, with particular emphasis on ethical challenges, privacy protection, and the urgency of cyber legislative reform. This research employs a qualitative normative legal approach using library research methods. The study examines primary legal materials, including the Indonesian Criminal Code, the Electronic Information and Transactions Law (UU ITE), and the Personal Data Protection Law, complemented by secondary sources such as academic journals, books, and legal commentaries. Data were analyzed using a descriptive-analytical and qualitative content analysis approach. The findings reveal that although the new Criminal Code represents an important step toward addressing cybercrime, its implementation remains constrained by overlapping regulations, limited institutional capacity, inadequate digital forensic expertise, and the absence of harmonized legal standards. The study also demonstrates that ethical issues, including digital surveillance, algorithmic accountability, and personal data protection, have become central concerns in enforcing digital criminal law. Furthermore, fragmented legal provisions concerning cybercrime and privacy require comprehensive legislative reform supported by stronger institutional coordination and international cooperation. The study concludes that effective digital criminal policy must integrate legal certainty, technological adaptability, ethical governance, and human rights protection. Strengthening digital literacy, improving law enforcement capacity, and harmonizing cyber legislation are essential to establishing a modern, fair, and sustainable digital criminal justice system capable of addressing contemporary technological challenges.